ASPEK GENUINE, CHANGE DAN DEVELOPT DARI FILSAFAT HUKUM ISLAM (TELAAH TEORI SEJARAH DEVIN DEEWES) - A, Asmawi (IAIN Tulungagung, 2018)
ABSTRACTSeeing from the prespectives of Deewes, the Prophetâs and Shahabahâs era constitute the era of developing the foundation of Islamic law. In other words, this era is considered as the genuine era of Islamic law implementation which employs the normative and rational approach to the text of Qurâan and Hadits. It can be said, then, that the phylosophy of Islamic law has been practiced since the era of the Prophet. In that era the development of Islamic law occurs in line with the cases in the community. This fact proves that there is a dialectic between the normative value of the text and social structure of the community in which the Islamic law applys. It shows that empirical experience is considered in the development of Islamic law. As the result, in the era of genuine implementation of Islamic law, the basis of Islamic law development is the texts of Quran and Hadits, rationalism of Ijma-Qiyas, and empirical approach of the sociological condition during the era of the Prophet and Shahabah.Keywords: Filsafat, History, Islamic